2011
DOI: 10.2304/ciec.2011.12.3.212
|View full text |Cite
|
Sign up to set email alerts
|

Avoiding Recolonisation in Early Childhood: Promoting Local Values as Mediators in the Spread of Globalisation

Abstract: This article seeks to draw attention to ways in which culturally based values and practices can and should influence implementation of globalised approaches to early childhood education and care across diverse contexts. Recent discussions have drawn attention to complexities associated with assimilation of globalised notions across diverse cultural contexts. This article is situated within such discussions, highlighting patterns of differentiation in the spread of globalisation across aspects of policy and pra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 32 publications
(89 reference statements)
0
6
0
Order By: Relevance
“…It is not our goal to distinguish the Eastern versus Western part of the curricular and pedagogical practices at E-KG. The current study goes beyond and to some extent, demonstrates the value of importing and adapting educational principles and curriculum models to diverse ways of life, as globalisation has resulted in rich diversity (Pearson, 2011). In particular, the study investigated ways in which a balance between change and tradition, East and West, the local and the global, can be achieved and maintained.…”
Section: Further Explanations From the Cultural-institutional Planementioning
confidence: 92%
“…It is not our goal to distinguish the Eastern versus Western part of the curricular and pedagogical practices at E-KG. The current study goes beyond and to some extent, demonstrates the value of importing and adapting educational principles and curriculum models to diverse ways of life, as globalisation has resulted in rich diversity (Pearson, 2011). In particular, the study investigated ways in which a balance between change and tradition, East and West, the local and the global, can be achieved and maintained.…”
Section: Further Explanations From the Cultural-institutional Planementioning
confidence: 92%
“…Glocalized learning and teaching refers to the curricular considerations and pedagogical framing of local and global community connectedness in relation to social responsibility, justice and sustainability. Illustrative cases and arguments for the importance of local communities' influence on implementation of globalised approaches to ECE have also been highlighted by researchers globally for some time (e.g., Chaiklin & Hedegaard, 2005;Hedegaard, 2014;Freitas, Terri, Shelton & Sperb, 2009;Nsmnang, 2009;Ødegaard, 2015;Pearson, 2011;Rogoff, 2003;Simpson, Lumsden & Clark, 2014;Tudge & Wanga, 2009).…”
Section: 'Glocalisation' -Revisiting the Global And The Local In Earlmentioning
confidence: 98%
“…Tobin (2011) further concluded that the implicit cultural influence is undervalued and deserves more awareness. It was even proposed that values and practices originated from the local culture could be promoted to mediate the implementation and effects of imported curriculum ideals to avoid cultural colonization in educating young children (Pearson, 2011).…”
Section: Education Reform: From Globalization To Glocalizationmentioning
confidence: 99%